Uniaxial tensile and impact investigation of carbon-fabric/polycarbonate composites with different weave tow widths. (5th October 2017) - Yang, Binbin; Lu, Longsheng; Liu, Xiaokang; Xie, Yingxi; Li, Jingwen; Tang, Yong
Abstract: Flexible thermoplastic composites hold great potential in the automobile industry due to their high specific strength and modulus, good recyclability and high productivity. In this work, a novel single-layered ultra-thin (≤ 0.3 mm thick) carbon-fabric/polycarbonate composite was laminated with two thin polycarbonate (PC) films as the matrix and a woven carbon fabric as reinforcement, adopting a balanced plain weave method combined with a hot-press technique. For the carbon fiber (CF) tow, thousands of filaments are packed with high density in a tape shape so that the permeation resistance of the matrix during hot-press increases, especially for a low molding temperature, inducing poor CF-PC bonding. To address this matter, raw CF tows were spread into a fabric prior to weaving. Three spread CF tows, 8, 14, and 20 mm in width, were used to investigate the effect of the tow width on the tensile strength and impact properties of the as-prepared composites. The experimental results showed that the 20 mm wide tow performed better with respect to normalized tensile strength, shear strength, peak force and penetration energy than the 8 and 14 mm tows, which can be attributed to its enhanced impregnation between the CF and PC matrix. Graphical abstract: Highlights: A single-layered ultra-thin carbon fabric/polycarbonate composite was fabricated. Spread carbon fiber tow improves the carbon fiber-matrix adhesion. Normalized tensile properties of the composite increase with the tow width. Normalized impact properties of the composite increase with the tow width.